Effect of hand massage on anxiety levels before contraceptive device installation in prospective IUD and implant users - Masruroh Masruroh; Istri Yuliani; Eko Mindarsih; B Verawati (Alma Ata University Press, 2026)
Background: Anxiety prior to contraceptive insertion is commonly experienced by prospective family planning acceptors. Psychological discomfort during the procedure may reduce client comfort, influence decision-making, and potentially affect the continuity and effectiveness of contraceptive use. In many clinical settings, anxiety management is often limited to verbal reassurance, while simple non-pharmacological approaches are rarely implemented. One technique that has received increasing attention is hand massage, which may promote relaxation through stimulation of peripheral nerves and improved blood circulation. This intervention is simple, inexpensive, and easy to apply in routine healthcare services. Objectives: This study aimed to examine the effect of hand massage on reducing anxiety levels among prospective intrauterine device (IUD) and implant acceptors at the Independent Midwife Practice of Istri Yuliani, Sleman. Methods: This research employed a quasi-experimental design with a one-group pre-test and post-test approach to examine changes before and after the intervention. This research employed a quasi-experimental design with a one-group pre-test and post-test approach to examine changes before and after the intervention A total of 56 prospective contraceptive acceptors participated in the study. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the hand massage intervention. The massage was administered prior to contraceptive insertion as a relaxation technique. Data analysis was performed using descriptive statistics to describe the distribution of anxiety levels and paired t-test to examine the significance of anxiety reduction following the intervention. Results: Before the intervention, 75% of respondents experienced mild anxiety, while only 3.6% reported no anxiety symptoms. After receiving hand massage, the proportion of respondents without anxiety symptoms increased substantially to 80.4%, whereas mild anxiety decreased to 19.6%. The paired t-test indicated a statistically significant reduction in anxiety scores (p = 0.001). Conclusions: Hand massage is associated with a reduction in anxiety prior to contraceptive insertion. This technique may serve as a supportive non-pharmacological intervention to enhance client comfort and improve the overall experience of family planning services.